Proposal of a Model for the Management of Changes in the Design Phase of Public Works of Educational Infrastructures Based on the BIM and ICE Methodologies - Sardi, Andrea Natalia Valderrama (2024)
The construction industry is essential for the economic development of a country. However, changing management in these projects can be complex due to communication between different stakeholders. Construction changes are common and can occur at any stage of the project, which can have negative impacts on costs and schedules. It is important to have clear communication of the vision and benefits of changes before implementing them. The use of Information and Communication Technologies (ICT) in construction can improve communication, collaboration, knowledge management, and acquisition processes. In this context, a change management model is proposed in the design phase of infrastructure works based on the BIM (Building Information Modeling) and ICE (Interactive Concurrent Engineering) methodologies. The model is divided into six phases: search and compilation of information, analysis of causes, design of the management model, test and validation of the model, analysis of results, and final adjustment of the model. The proposed model uses BIM tools and concepts and ICE sessions to improve the flow of information and the organizational relationship between participants in the design phase of construction works. In summary, the proposed model seeks to address the complexities of change management in construction through the use of BIM methodology and ICE sessions, improving communication and coordination between the different actors involved in infrastructure projects.